A fuzzy multi-attribute decision making model for flood control project selection - Binyamin Yusoff (Fakulti Sains dan Teknologi, 2012)
Flood management comprises different water resources activities aimed at reducing potential harmful impacts of floods. One of the most critical decisions in flood management is selection of flood control project. Selection of flood control project is typically a complex process, characterized by trade-offs between social, environment, economic and technical aspects. Moreover the decision making process involve a group of experts in which there have difference opinions or conflict perceptions about the project.